Vulnerability and resilience in the face of climate changes in Senegal's drylands: measurement at the household level and determinant assessment - Yessoufou, Adjani Nourou-Dine; Kumar, Shalander; Houessionon, Prosper; Worou, Omonlola Nadine; Wane, Abdrahmane; Whitbread, Anthony (Frontiers in Climate, 2024)
The resilience capacity of the smallholder households is one of the main drivers of their ability to continue to farm and make investments in the fragile dryland regions. This paper aims to assess the resilience profile of smallholder farmers in the face of climate change and the factors influencing it in three dryland sub-regions of Senegal: Louga, Kaffrine and Thies. We developed a composite index of climate resilience (CICR) using data on farmers' perception of climate variability and their perceived ability to withstand, adapt and bounce back in the event of climatic shocks. Drought, strong winds and soil fertility decline because of climate change came out as the main climate hazards impacting the smallholder farming systems. The CICR value ranged from -2 for most vulnerable households to +2 for most resilient households. On average all the households were found to be vulnerable with an average CICR value of -0.2. LOUGA region was the most vulnerable with an average CICR value of -0.36; followed by THIES (-0.2). The KAFFRINE region was relatively less vulnerable with a CICR value of -0.1. Ordered logit model estimates show that the chances to improve CICR decrease with the increase of household's head age until the age of 59. Access to training on climate-smart agricultural (CSA) practices and climate information appeared to have the potential to increase by 171% the chance of the household improving its resilience status. Analysis also shows that one more woman working offfarm or in home-gardening has the potential to multiply by 4 the chances of households to be more resilient Highlighting the importance of empowering women for enhancing household resilience to climate change. The off-farm revenue increased the chance to improve the resilience status of the farm household by 62% and receipt of transfer revenue by 50%. This study provides a robust method for quantifying the resilience or well-being and its drivers and enriches our understanding of the resilience ability of farmers to climate change in a West Africa context. It can be useful in designing effective adaptation interventions and improve the overall well-being of smallholder farmers.